If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 4) + -2x = x + 17 Reorder the terms: 2(4 + 3x) + -2x = x + 17 (4 * 2 + 3x * 2) + -2x = x + 17 (8 + 6x) + -2x = x + 17 Combine like terms: 6x + -2x = 4x 8 + 4x = x + 17 Reorder the terms: 8 + 4x = 17 + x Solving 8 + 4x = 17 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 8 + 4x + -1x = 17 + x + -1x Combine like terms: 4x + -1x = 3x 8 + 3x = 17 + x + -1x Combine like terms: x + -1x = 0 8 + 3x = 17 + 0 8 + 3x = 17 Add '-8' to each side of the equation. 8 + -8 + 3x = 17 + -8 Combine like terms: 8 + -8 = 0 0 + 3x = 17 + -8 3x = 17 + -8 Combine like terms: 17 + -8 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| 3f=999 | | 3-4[2-(5y-8)]= | | 4x-3x-6=21 | | -7-3x=8+2 | | 4x+x-3x+7=2x+x | | 8(x+.5)=2x+4 | | -5(2x-9)=2(x-8) | | 4x^2-10=-6x | | 2c+4-3c=-9+c+15 | | 7C+1=50 | | x-4.5=3 | | 10.6p+15=205.8 | | 10=50x | | 8s-12=52 | | -x-3x+20=x | | 3xyz-y+4x-y= | | 45p=168 | | 2f-81=11 | | 27=x+14 | | -36-9x=-12x+3 | | (5x-2)(7x+8)= | | 2(1/2x+1)=-3(2x-1)+4(2x+1) | | -8x+-3x= | | 2x=3x-22 | | 3r-7=17r | | 400p+20=680 | | 2x+x+2x=126 | | 32.8=8n | | 9s=-20 | | (-3+2i)-(4-4i)= | | 7-2p=12p | | (8x^2-3x^3)-(2x^2-5x^3)= |